Newborn care in Nepal: the effects of an educational intervention on nurses' knowledge and practice. (21st April 2013) - Shrestha, S.; Petrini, M.; Turale, S.
<x xml:space="preserve">Abstract</x> Aim To determine the effectiveness of an educational intervention for improving nurses' knowledge and practice regarding newborn care in Kathmandu, Nepal. Background Four million neonatal deaths occur annually, especially in developing countries. In 2010 in Nepal, the neonatal mortality rate was 28/1000 births. Modern nursing and research education is still developing in Nepal, but the country's nurses are in a unique position to help combat avoidable morbidity and mortality. This study was designed to assist nurses working in maternity units to obtain and/or sustain knowledge and competence in practice to ensure the health and safety of vulnerable newborns, and thereby to help reduce mortality and morbidity. Theoretical Framework Concepts from the Transtheoretical Model of behaviour change developed in the USA informed this study in the belief that an educational intervention would assist in behaviour changes in nurses caring for newborns. Design Quasi‐experimental, time‐series pre‐test/post‐test. Setting Maternity and women's hospitals in Kathmandu, Nepal. Participants Convenience sample of 30 nurses working in emergency room, delivery room and birthing centre. Methods Nurses were measured on study outcomes at multiple time points: before a self‐directed educational intervention and discussion, immediately, 1 and 3 months after intervention. Data were collected using three instruments: a demographics questionnaire, the Knowledge Survey Questionnaire and the Skills Learning Checklist (SLC). The SLC was completed during nursing practice in observations by the researcher. Results Significant findings suggested that this educational intervention was effective for improving nurses' knowledge and practice regarding newborn care, and there was a positive correlation between knowledge and practice. Conclusion This was the first study of its kind in Nepal, a small step in enhancing nurses' abilities to improve their knowledge and competence regarding care of newborns. However, continued education and guidance are required to sustain knowledge and competence in practice, and our educational intervention needs further testing with other populations of nurses. There are various policy implications required to enable this to happen. This includes health ministry funding and support for in‐service education; hospitals and universities working together to offer in‐service education, competency testing and revised curricula; and nurse registering authorities requiring ongoing nurse education programmes and competency testing.